2015
DOI: 10.1038/srep17331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proximal versus distal 50% enterectomy on nutritional parameters in rats preconditioned with a high-fat diet or regular chow

Abstract: Obesity may protect against the nutritional consequences of short bowel syndrome. We hypothesized that rats preconditioned with an obesogenic diet would have better outcomes after surgical induction of short bowel syndrome compared to rats on regular chow. Rats were fed a high-fat diet or regular rat chow for six months, and then underwent 50% proximal, 50% distal, or sham enterectomy. Food intake, weight, and body composition were monitored before and for 4 weeks after surgery. The high-fat diet consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(26 citation statements)
references
References 36 publications
1
24
1
Order By: Relevance
“…A sudden increase in food intake was observed in GK-S-30R (the group that has short bowel because of 30-cm small bowel resection) 6 wk after operation. Nutritional adaptations have been reported following small bowel resection in rats, including increased food intake, hyperplasia of remaining bowel remnant, and reduced gastric-inhibitory peptide secretion 30,31 . The sudden increase in our study in food intake in GK-S-30R after 6 wk may reflect an adaptation response to small bowel resection.…”
Section: Discussionmentioning
confidence: 99%
“…A sudden increase in food intake was observed in GK-S-30R (the group that has short bowel because of 30-cm small bowel resection) 6 wk after operation. Nutritional adaptations have been reported following small bowel resection in rats, including increased food intake, hyperplasia of remaining bowel remnant, and reduced gastric-inhibitory peptide secretion 30,31 . The sudden increase in our study in food intake in GK-S-30R after 6 wk may reflect an adaptation response to small bowel resection.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the present study (which utilized a 75% enterectomy) demonstrated a large effect of resection on body composition in comparison to sham resection; the prior 2015 study (which utilized a 50% enterectomy), was unable to demonstrate such a differential effect. 10 Regarding secondary conclusion number 2, the low-fat diet rats in the present study had greater percent body fat (25%) compared to the 18% body fat of similarly-preconditioned rats from the 2015 study (same rat strain). 10 It is not clear why the low-fat diet rats in the present study attained this relatively high preoperative percent body fat, or whether these rats were "lean enough" to qualify as a "non-obese" comparator group for the rats on the high-fat diet.…”
Section: Discussionmentioning
confidence: 57%
“…[27][28][29][30][31] In addition to the evaluation of lean mass as the primary endpoint, there are secondary endpoints that could have been evaluated in the present study, including food intake, intestinal adaptation, immunohistochemical staining, serum peptide levels, and other nutrition-relevant serum tests; of note, most of these secondary endpoints were examined in the 2015 study. 10 We elected not to perform these analyses in the current study, because: (1) the relevance of these secondary endpoint data would not be clear, as the study was negative with respect to the primary endpoint; and (2) we did not want to expend resources in the pursuit of costly secondary endpoint data which would have doubtful relevance. In summary, this was a report of a second study in which the effect of pre-resection obesity on preservation of lean body mass after massive intestinal resection was tested in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations